Ecologia da polinização de Humiria Balsamifera (AUBL.)A.S.T.HIL. e sua importância para composição poliníca e propriedades fisíco-quimícas do mel da meliponicultura maranhense. - PINTO, Rafael Sousa (2020)
Humiria balsamifera has been considered an important source of nectar for honey production on the eastern coast of Maranhão, but little is known about this plant, and in this work, we seek to study aspects of the pollination ecology of the species in the Lençóis Maranhenses National Park (PNLM), and to understand its contribution to the composition of the pollen spectrum and properties of stingless bee honey. In 2017, the reproductive phenophases of H. balsamifera were observed, and these occurred in all months of the year. Flowering was not associated with abiotic factors, but the production of immature fruits increased in the dry season. The main resource offered to floral visitors was nectar, sought by 49 morpho-species distributed in Hymenoptera, Diptera, Lepidoptera, Coleoptera and Passeriformes. Bees had the highest wealth (17 species) and abundance (89% of the total). The most representative were the social bees, and also Xylocopa cearensis and Megalopta amoena, two solitary species. The activity of the bees occurred throughout the year, and in general, there was a positive correlation between the increase in visits and the intensity of flowering. The pollen analysis of the bees' body revealed 22 pollen types. Social species had the highest frequency of homospecific pollen from the plant. The analysis of the interaction network showed a nested structure, indicating the contribution of H. balsamifera to the stability of bee biodiversity in the area. A monthly analysis of honey from Melipona subnitida and Melipona fasciculata in PNLM showed the occurrence of 56 pollen types in their honeys, with M. subnitida greater richness, diversity and uniformity of pollen types. When making an exclusion of pollen types belonging to species that do not offer floral nectar, we found that H. balsamifera was the main nectariferous source in the period, mainly for M. fasciculata. Other species also stood out like Chrysobalanus icaco, Protium heptaphyllum and Coccoloba. In 2019, 17 honey samples were obtained of different bees (M. fasciculata, M. flavolineata, M. subnitida, Apis mellifera) from the cities of Morros, Belágua and Barreirinhas. In all samples, pollen from H. balsamifera was present, but only in three of them did it occur with a frequency above 45%. In six other samples, some other pollen appeared as dominant. The physical-chemical, microbiological and antioxidant activity analyzes showed good quality of the honeys, although the humidity was high for samples of stingless bees, something normal for these species. The analyzes of color, pH, free acidity, electrical conductivity, ash, total phenols, total flavonoids, antioxidant activity (DPPH and FRAP) were sufficient to show by PCA 75.21% of the sample variance. Particularly, the stingless honeys from Belágua and Morros differed from the samples from Barreirinhas and Apis mellifera, and seemed to show that in these honeys H. balsamifera predominates over other botanical sources. The electrical conductivity, an important analysis to characterize the botanical and geographical origin of honey, indicated that 88.2% of the honeys in the 3 cities have values above 0.8mS/cm. We didn’t obtain conclusive results regarding the contribution of H. balsamifera to the properties of honey, but we were able to confirm that the pollen of the species occurs in all samples and is an important source of nectar. The association of H. balsamifera with meliponiculture must be valued because the plant blooms continuously and bees are seen all year round in its flowers, and while the species maintains a rich fauna of floral visitors, it benefits from them, already which depends on the animals to carry out their cross-pollination.